Limitation of the Punishment of Caning in Open Places in Aceh - Muhammad Syarif (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2022)
The provisions for the implementation of caning in an open place that can be witnessed by many people are contained in the Qur'an letter an – Nur verse 2. In practice in Aceh, the application of the punishment of caning is still getting serious focus on the interpretation of the open place and the number of people who witness. In the Governor's regulation Number 5 of 2018 it is stated that what is meant by open spaces in Correctional Institutions. This study will review the reasons for changing the caning sentence to prisons, the provisions of Islamic law related to the location of the caning, and the relevance of the implementation of the caning punishment to the legal awareness of the community. This research is a normative legal research with primary, secondary, and tertiary legal materials with descriptive data analysis. The data collection technique uses the study of normative documents of Islamic law and is associated with regulations. The results showed that changes in the implementation of the caning sentence to prisons were made to be more orderly, not watched by minors, did not record the execution process, let alone send it to social media. In addition, to protect the human rights of the convict. The execution of the caning according to the provisions of Islamic law must be witnessed by a group or at least several believers and must be in an open place. The implementation of caning in Aceh certainly reaps many pros and cons both academically, practical and ordinary people, both at the local, national and even international levels. On the other hand, the implementation of caning is still considered not optimal and not effective. The issue of politicization, lack of legal awareness, imbalance in the application of punishment. Especially in a closed place Correctional Institutions, of course there is another purpose of witnessing the caning, both psychological punishment for the convict and educational value for those who witness it.Ketentuan pelaksanaan hukuman cambuk di tempat terbuka yang dapat disaksikan oleh banyak orang terdapat dalam al-Qur’an surat an-Nur ayat 2. Dalam praktekknya di Aceh, pelaksanaan hukuman cambuk masih mendapatkan perdebatan serius mengenai tafsiran tempat terbuka dan jumlah orang yang menyaksikan. Dalam peraturan Gubernur Nomor 5 Tahun 2018 meyebutkan bahwa yang dimaksud dengan tempat terbuka di Lembaga Pemasyarakatan. Kajian ini akan mengulas terkait alasan perubahan pelaksanaan hukuman cambuk ke Lapas, ketentuan hukum Islam terkait lokasi pelaksanaan hukuman cambuk, dan relevansi pelaksanaan hukuman cambuk dengan kesadaran hukum masyarakat. Penelitian ini merupakan penelitian hukum normatif dengan bahan hukum primer, sekunder, dan tersier dengan analisis data deskriptif. Teknik pengumpulan data menggunakan studi dokumen normatif hukum Islam dan mengaitkan dengan regulasi aturan. Hasil penelitian menunjukkan bahwa perubahan pelaksanaan hukuman cambuk ke Lapas agar lebih tertib, tidak ditonton oleh anak di bawah umur, tidak merekam proses eksekusi, apalagi sampai membagikan ke media sosial. Selain itu, untuk melindungi HAM terpidana. Pelaksanaan eksekusi cambuk menurut ketentuan hukum Islam wajib disaksikan oleh sekelompok atau minimal beberapa orang beriman dan harus tempat terbuka. Pelaksanaan hukuman cambuk di Aceh tentunya banyak menuai pro dan kontra baik akademisi, praktisi maupun masyarakat biasa, baik tingkat lokal, nasional bahkan internasional. Disisi yang lain, pelaksanaan hukuman cambuk masih dinilai belum optimal dan belum efektif. Isu politisasi, kurang kesadaran hukum, ketidakseimbangan penerapan hukuman menjadi alasan yang dapat dijelaskan. Apalagi di tempat tertutup (Lembaga Pemasyarakatan), tentu tidak ada lagi tujuan dari mempersaksikan hukuman cambuk, baik hukuman psikologis bagi terhukum maupun nilai edukasi bagi yang menyaksikannya.